Effectiveness of Short-Term Psychodynamic Therapy on Negative Meta-Emotion and Marital Burnout in Betrayed Women - Khodadad, Farzam; Agah Heris, Mojgan; Rahmanian, Mahdieh; Kordmirza Nikoozadeh, Ezzatollah (Psychology of Woman Journal, 2025)
Objective: The aim of this study was to investigate the effectiveness of short-term psychodynamic therapy on negative meta-emotion and marital burnout in women who have experienced infidelity.Materials and Methods: This research employed a quasi-experimental design with a pretest-posttest control group format and a two-month follow-up phase. The statistical population included women affected by infidelity who sought counseling services in Borujerd in 2024. The sample consisted of 30 women selected through convenience sampling and randomly assigned to either an experimental or a control group (15 participants per group). The intervention group received short-term psychodynamic therapy in nine weekly sessions lasting 75 minutes each. Data were collected using the Meta-Emotion Scale (MES) developed by Mitmansgruber et al. (2009) and the Couple Burnout Measure (CBM) developed by Pines (1996). Data analysis was conducted using repeated measures analysis of variance (ANOVA).Findings: The results indicated that short-term psychodynamic therapy significantly improved negative meta-emotion and marital burnout in women who had experienced infidelity (p < .05).Conclusion: It is concluded that short-term psychodynamic therapy is effective in improving negative meta-emotion and marital burnout in betrayed women.